Influencing factors of HCV testing willingness among men who have sex with men in China: A structural equation modeling analysis - Jiayan Li; Jing He; Guohui Yang; Zhen Cao; Xiaoni Zhong (PLoS ONE, 2025)
Background Men who have sex with men (MSM) are a population with greater likelihood of the hepatitis C virus (HCV). Early detection of HCV status is beneficial to therapy and prevention of the further transmit of HCV. The testing rate of HCV in MSM is low, so it is important to investigate the factors that influence testing willingness in order to increase the testing rate. Objectives Based on the health belief model (HBM), this study investigated the influencing factors of HCV testing willingness among MSM, and provided a basis for promoting HCV testing among MSM. Methods Non-probability sampling was employed to collect samples, and electronic questionnaires were used to perform cross-sectional surveys on the samples, including socio-demographic characteristics, sexual behavior characteristics, HCV testing willingness and HBM scale. The data was evaluated with a structural equation model (SEM). Results Result of the 857 MSM, 55.7% had ever undergone HCV testing, 90.9% were willing to undergo HCV testing in the future, and 71.7% were anticipated to undergo HCV testing within the next six months. The SEM's findings demonstrated that behavioral intention was positively impacted by self-efficacy (β =  0.482, p <  0.001) and perceived susceptibility (β =  0.312, p <  0.001), while behavioral intention was negatively impacted by perceived barriers (β =  -0.254, p <  0.001). Furthermore, behavioral intention was indirectly impacted by perceived benefits (β =  0.309, p <  0.001) and perceived barriers (β =  -0.139, p <  0.001), with self-efficacy acting as a mediating factor. Conclusion Self-efficacy, perceived susceptibility, benefits, and barriers predict behavioral intention. These findings can inform the development of methods to increase MSM willingness to identify HCV.